Potential Contributions to Geoscience from GNSS Observations of the King Edward Point Geodetic Observatory, South Georgia, South Atlantic Ocean - TEFERLE, Felix Norman; HUNEGNAW, Addisu; AHMED, Furqan; SIDOROV, Dmitry; Williams, Simon; Foden, Peter; Woodworth, Phil (2013)
During February 2013 the King Edward Point (KEP) Geodetic Observatory was established in South Georgia, South Atlantic Ocean, through a University of Luxembourg funded research project and in collaboration with the United Kingdom’s National Oceanography Centre, British Antarctic Survey and Unavco, Inc. Due to its remote location in the South Atlantic Ocean, as well as, being one of few subaerial exposures of the Scotia plate, South Georgia Island has been a key location for a number of global monitoring networks, e.g. seismic, geomagnetic and oceanic. However, no geodetic monitoring station has been established, e.g. by the International Global Navigation Satellite System (GNSS) Service (IGS) community, despite the lack of such observations from this region. In this study we will present an evaluation of the GNSS observations from the KEP Geodetic Observatory for the period from February to August 2013. We calculate multipath and positioning statistics and compare these to those from IGS stations. The on-site meteorological data is compared to those from the nearby KEP meteorological station and global numerical weather models, and the impact of these data sets on delay and integrated water vapour estimates will be evaluated. We will discuss the installation in terms of its potential contributions to sea level observations using tide gauges and satellite altimetry, studies of tectonics, glacio-isostatic adjustment and atmospheric processes. GSCG